Characterization of disease-specific alterations in metabolites and effects of mesenchymal stromal cells on dystrophic muscles - Nitahara-Kasahara, Yuko; Posadas-Herrera, Guillermo; Hirai, Kunio; Oda, Yuki; Snagu-Miyamoto, Noriko; Yamanashi, Yuji; Okada, Takashi (Frontiers in Cell and Developmental Biology, 2024)
Introduction Duchenne muscular dystrophy (DMD) is a genetic disorder caused by mutations in the dystrophin-encoding gene that leads to muscle necrosis and degeneration with chronic inflammation during growth, resulting in progressive generalized weakness of the skeletal and cardiac muscles. We previously demonstrated the therapeutic effects of systemic administration of dental pulp mesenchymal stromal cells (DPSCs) in a DMD animal model. We showed preservation of long-term muscle function and slowing of disease progression. However, little is known regarding the effects of cell therapy on the metabolic abnormalities in DMD. Therefore, here, we aimed to investigate the mechanisms underlying the immunosuppressive effects of DPSCs and their influence on DMD metabolism. Methods A comprehensive metabolomics-based approach was employed, and an ingenuity pathway analysis was performed to identify dystrophy-specific metabolomic impairments in the mdx mice to assess the therapeutic response to our established systemic DPSC-mediated cell therapy approach. Results and Discussion We identified DMD-specific impairments in metabolites and their responses to systemic DPSC treatment. Our results demonstrate the feasibility of the metabolomics-based approach and provide insights into the therapeutic effects of DPSCs in DMD. Our findings could help to identify molecular marker targets for therapeutic intervention and predict long-term therapeutic efficacy.